MINAT MASYARAKAT BERINVESTASI EMAS PADA PEGADAIAN SHARIâAH DI LOMBOK - Rosyidah, Umu (LP2M IAIN Mataram, 2014)
During this time, pawnshop is one of a financial solution for the people who have financial problems in general, so as to the people in Lombok. However, there is a question about one of the form of the service of the pawnshop i.e. gold investment, is such investment product anxiously taken the interest of Lombok people especially in sharia pawnshop? Therefore this research is conducted to answer the question. This research applies quantitative approach with survey method, while in determining the samples, accidental sampling is selected and to gather primary data, questionnaire method is applied as well. In analyzing the data, the researcher applies inferential statistics non parametric. This research shows that, both in partially and simultaneously investment, investment risk and Islamic products have significant influence upon the interest of the people on gold investment in sharia pawnshop. This could be happened because of some possible factors, one of which is some dominant factors that influence the people to invest their money in gold such as profit possibilities, experiences â positive experiences (the intensity of obtaining profit) in gold transaction. Meanwhile sharia factors which free from riba, gharar, and though the bound to ideological thinking or religion is one of the factors that increases the interest of the people in gold investment in sharia pawnshop